Impact of Using Tenggarong Sand and Lightweight Brick Waste in the Production of Pavement Paving Blocks - Liana, Ulwiyah Wahdah Mufassirin; Noor, Muhammad (JSE Journal of Science and Engineering, 2024)
The development of construction encourages increased development so as to create innovations in the development, one of which is used of road pavement materials which were originally dominated by asphalt, has now varied with paving blocks. Using waste as a mixture in making paving blocks is an alternative to creative and innovative products. In this case making paving blocks with brick waste, the waste increases along with the number of lightweight brick enthusiasts. The purpose article is to determine the strength value of paving blocks made from brick waste and tenggarong sand as a mixture of lightweight brick waste. The mixing ratio of cement and sand used was 1:6 with variations in the mixture of lightweight brick waste 0%, 25%, 50%, 75% and 100%. The tests carried out were water absorbtion and compressive strength. Data collection by testing in the laboratory on the materials used are sand tenggarong, cement three wheels and CLC lightweight brick waste. The results show that the most optimal percentage of the use of brick waste is at a percentage of 25% at the age of 28 days has a compressive strength value of 28.85 Mpa thus included in the quality of class B (parking lot). While the other percentages do not match between the compressive strength and the absorbtion value that has been determined. Research on compressive strength and water absorbtion of paving blocks can be the basis for further research such as testing the wear of paving blocks using brick waste as a mixture.